EFEKTIVITAS PENGGUNAAN MEDIA E-LEARNING BERBASIS GOOGLE SITES DALAM PEMBELAJARAN FOTOGRAFI - First Gerald Noviano; Yatim Riyanto; Hari Sugiharto Setyaedhi (Akademika, 2023)
This study aimed to determine the effectiveness of using Google Sites-based e-learning media to learn photography. The research method used is a quantitative research method with a one-group pre-test and post-test experimental research design. Researchers collected data through tests on 24 students in class XI Multimedia at Wijaya Putra Vocational School. Data analysis was performed using the T test, Based on the results of the t test on the output table of the paired sample test, it was found that the value of Sig. (2-tailed) was 0.000 < 0.05. This shows that there is a significant difference between learning outcomes in pre-test and post-test scores after using e-learning media based on Google Sites. As a suggestion for further research, in addition to testing student learning outcomes variables, research can consider the application of Google Sites in increasing student learning motivation and independence.